Model Project Based Learning dalam Pembelajaran Daring di SMP Negeri 5 Wadaslintang - Fahrus Widodo; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2022)
During the Covid-19 pandemic, the world of education developed and changed very fast and rapidly, so it needed to adjust and improve the quality of education itself. The online learning process in SMP Negeri 5 Wadaslintang included the use of media, methods, and learning models that are in accordance with current technological developments, one of which is the Project Based Learning model in social studies learning. The purpose of this study was to determine student participation and learning activities in online learning during the Covid-19 pandemic. The method used in this research is literature study. This method was chosen because of the short research time and to find references to theories that are relevant to the case or problem found. In online learning at SMP Negeri 5 Wadaslintang, the use of the Project Based Learning model in social studies subjects has increased student learning activities, although some of them have network problems and device limitations. The use of the Project-Based Learning model makes learning more conducive and fun. The use of the Project Based Learning learning model in social studies subjects can increase student learning activities, so that the learning process is more conducive and fun.